Drug Resistance and Pseudoresistance - Tilo Großer; Susanne Fries; John A. Lawson; Shiv Kapoor; Gregory R. Grant; Garret A. FitzGerald (2012)
Background— Low dose aspirin reduces the secondary incidence of myocardial infarction and stroke. Drug resistance to aspirin might result in treatment failure. Despite this concern, no clear definition of aspirin resistance has emerged, and estimates of its incidence have varied remarkably. We aimed to determine the commonality of a mechanistically consistent, stable, and specific phenotype of true pharmacological resistance to aspirin—such as might be explained by genetic causes. Methods and Results— Healthy volunteers (n=400) were screened for their response to a single oral dose of 325-mg immediate release or enteric coated aspirin. Response parameters reflected the activity of the molecular target of aspirin, cyclooxygenase-1. Individuals who appeared aspirin resistant on 1 occasion underwent repeat testing, and if still resistant were exposed to low-dose enteric coated aspirin (81 mg) and clopidogrel (75 mg) for 1 week each. Variable absorption caused a high frequency of apparent resistance to a single dose of 325-mg enteric coated aspirin (up to 49%) but not to immediate release aspirin (0%). All individuals responded to aspirin on repeated exposure, extension of the postdosing interval, or addition of aspirin to their platelets ex vivo. Conclusions— Pharmacological resistance to aspirin is rare; this study failed to identify a single case of true drug resistance. Pseudoresistance, reflecting delayed and reduced drug absorption, complicates enteric coated but not immediate release aspirin administration. Clinical Trial Registration— URL: http://www.clinicaltrials.gov . Unique identifier: NCT00948987.